2017
DOI: 10.1016/j.stemcr.2016.12.026
|View full text |Cite
|
Sign up to set email alerts
|

GATA6 Plays an Important Role in the Induction of Human Definitive Endoderm, Development of the Pancreas, and Functionality of Pancreatic β Cells

Abstract: SummaryInduced pluripotent stem cells were created from a pancreas agenesis patient with a mutation in GATA6. Using genome-editing technology, additional stem cell lines with mutations in both GATA6 alleles were generated and demonstrated a severe block in definitive endoderm induction, which could be rescued by re-expression of several different GATA family members. Using the endodermal progenitor stem cell culture system to bypass the developmental block at the endoderm stage, cell lines with mutations in on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
91
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 46 publications
6
91
0
Order By: Relevance
“…[65][66][67][68] The expression of GATA4 and GATA6 in hPSC differentiation cultures has been recently reported. 69,70 Both GATA4 and GATA6 were found to be coexpressed at the definitive endoderm as well as early pancreatic progenitor stages, similar to what it is observed in mice. As pancreatic progenitor cells differentiate into ß-like cells, GATA4 and GATA6 expression decrease (particularly GATA6) with no substantial expression in mature insulinsecreting cells.…”
Section: Human Pluripotent Stem Cells Differentiation Studies On Gasupporting
confidence: 73%
See 3 more Smart Citations
“…[65][66][67][68] The expression of GATA4 and GATA6 in hPSC differentiation cultures has been recently reported. 69,70 Both GATA4 and GATA6 were found to be coexpressed at the definitive endoderm as well as early pancreatic progenitor stages, similar to what it is observed in mice. As pancreatic progenitor cells differentiate into ß-like cells, GATA4 and GATA6 expression decrease (particularly GATA6) with no substantial expression in mature insulinsecreting cells.…”
Section: Human Pluripotent Stem Cells Differentiation Studies On Gasupporting
confidence: 73%
“…The recent development of protocols for stepwise differentiation of hESCs and induced pluripotent stem cells (hPSCs) toward β‐cells constitutes a relevant in vitro model for studying human pancreatic formation . The expression of GATA4 and GATA6 in hPSC differentiation cultures has been recently reported . Both GATA4 and GATA6 were found to be coexpressed at the definitive endoderm as well as early pancreatic progenitor stages, similar to what it is observed in mice.…”
Section: Human Pluripotent Stem Cells Differentiation Studies On Gatamentioning
confidence: 55%
See 2 more Smart Citations
“…Previous investigations of GATA6 in murine models have proven difficult due to early‐stage lethality . Using loss‐of‐function experiments in human PSCs, three separate groups have shown that GATA6 is essential for definitive endoderm formation . The use of PSCs allowed for the investigation of endoderm formation in isolation, negating lethality derived from different lineages, in a human context.…”
Section: Pscs As a Model Of Liver Developmentmentioning
confidence: 99%